Tiriti-Based Anti-Racism Praxis of Pākehā Critical Allies During Aotearoa Health System Reforms - Rae, Ngaire (Auckland University of Technology, 2025)
The overall aim of this research is to provide guidance to Pākehā working towards a Tiriti-honouring, equitable health system. This thesis explores the role of Pākehā allies during the reform of the colonial health system from mid-2021 through to mid-2023. The promise and potential of these reforms to transform the system to be more Tiriti-focused created a unique opportunity to study how Pākehā allies within the system contribute towards change. This study specifically explores efforts to address anti-Māori racism, pursue Tiriti implementation and improve Māori health. By focusing on the experiences of Pākehā, this study seeks to examine how those of us who are privileged by colonisation, white supremacy and racism can use this power to dismantle the systems of oppression. This study is a work of activist scholarship located in the transformative research paradigm and employing Te Tiriti as a methodology. As an activist scholar, I have remained connected and accountable to STIR: Stop Institutional Racism, the movement to end institutional racism in the public health system, and the Pākehā Tiriti workers movement through Network Waitangi Whangārei. I also had accountability to a critical research whānau who provided political, cultural and strategic advice throughout. The seven participants in this qualitative study were Pākehā (white New Zealanders of European descent), endorsed by the critical research whānau as allies (those committed to Tiriti justice, addressing anti-Māori racism and Māori health equity); all were leaders with influence in the health sector. The participants were interviewed three times, in late 2021, mid-2022 and mid-2023. The interviews were analysed using reflexive thematic analysis. This study makes a unique contribution within research processes: through the articulation of a deliberate relational citational praxis implemented within the literature review, a description of Te Tiriti as a methodology within the transformative research paradigm, and the expansion of reflexive thematic analysis to incorporate the reflections of both critical research whānau and participants. A significant contribution is the development of the Whiti Mai te Rā model which describes the Tiriti-based anti-racism praxis of Pākehā allies in the health system, building on existing work articulating Tiriti-based anti-racism. The Whiti Mai te Ra model contains five core concepts. The first is respect for, and action to uphold the rangatiratanga of Māori over Aotearoa. The second, ‘becoming consciously Pākehā’, involves a clearly articulated Pākehā cultural identity, formed and maintained in relation with Māori, accountable for Pākehā power and privilege recognising ourselves as beneficiaries of racism and colonisation, with an ethic of service orientation purposefully working to address racism and improve Māori health. This conscientised Pākehā identity informs a strategic, Tiriti-based anti-racism praxis that is unique to Aotearoa, that upholds the intent of Te Tiriti, enacts the articles, and is conducted in relation with Māori. Ongoing critical reflection and critical thinking contributes to both a conscious Pākehā identity and Tiriti-based action, which together form an iterative, continuous journey of development. The praxis is embraced by hope, love and courage combined with a commitment to genuine, respectful relationships.